Prevalence and associated risk factors of Strongyloides stercoralis infection in urban slum community of Dhaka, Bangladesh (Asian-Australasian Journal of Bioscience and Biotechnology, 2017)
The present study was designed to investigate Strongyloides stercoralis infestation in four selected slum areas of Dhaka city. Harada-Mori culture was applied for detection. The average prevalence of S. stercoralis infection was 13.42%; 11.77% in male and 13.85% in female. The highest prevalence was found (40%) among the slum dwellers aged 50-59 years old following the age group 10-19 years (16.66%). In summer, the prevalence was the lowest (2.50%) and the peak was in rainy season (33.33%). The infestation was significant (p